WOMEN WRITERS IN ENGLISH LITERATURE: PIONEERS, VOICES AND LEGACIES - UMIRZOQOVA SHAXRIZODA MIRXALIL QIZI; KHAMITOV ELDORBEK ERKIN O'G'LI (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article delves into the rich and diverse contributions of women writers in English literature throughout history. From the pioneering works of early trailblazers to the powerful voices of contemporary authors, women have played a pivotal role in shaping the literary landscape. Through an exploration of their diverse themes, innovative narrative techniques, and enduring legacies, this article sheds light on the profound impact of women writers on English literature.